2008
DOI: 10.1007/s00170-008-1753-5
|View full text |Cite
|
Sign up to set email alerts
|

A tabu search algorithm for two-sided assembly line balancing

Abstract: In a production facility there may be more than one straight assembly line located in parallel. Balancing of parallel assembly lines will provide the flexibility to minimize the total number of workstations due to common resource. This type of problem is called as parallel assembly line balancing (PALB) problem. In this paper, a tabu search based approach is proposed for PALB problem with aim of maximizing line efficiency (LE) (or minimizing number of stations) and minimizing variation of workloads (V). This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 34 publications
0
38
0
8
Order By: Relevance
“…Meta-heuristics have also been presented to address twosided assembly line balancing problem, i.e. Baykasoglu and Dereli (2008), Simaria and Vilarinho (2009), Ozcan and Toklu (2009b), Ozbakir and Tapkan (2010), Ozcan (2010), Ozbakir and Tapkan (2011), Chutima and Chimklai (2012). Among these meta-heuristics, the studies of Kim et al (2000Kim et al ( , 2009, Taha et al (2011), Purnomo et al (2013), and Rabbani et al (2012) employ different variations of genetic algorithm to balance two-sided lines.…”
Section: International Journal Of Production Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-heuristics have also been presented to address twosided assembly line balancing problem, i.e. Baykasoglu and Dereli (2008), Simaria and Vilarinho (2009), Ozcan and Toklu (2009b), Ozbakir and Tapkan (2010), Ozcan (2010), Ozbakir and Tapkan (2011), Chutima and Chimklai (2012). Among these meta-heuristics, the studies of Kim et al (2000Kim et al ( , 2009, Taha et al (2011), Purnomo et al (2013), and Rabbani et al (2012) employ different variations of genetic algorithm to balance two-sided lines.…”
Section: International Journal Of Production Researchmentioning
confidence: 99%
“…Cercioglu et al (2009) proposed a simulated annealing approach to solve PALBP and compared obtained results with the results of existing heuristic algorithm proposed by Gokcen et al (2006). Ozcan et al (2009) developed the first multi-objective tabu search algorithm for PALBP and tested the performance of the algorithm on a set of well-known problems in the literature. Scholl and Boysen (2009) modelled the PALBP mathematically and proposed an exact solution procedure.…”
Section: International Journal Of Production Researchmentioning
confidence: 99%
“…Different heuristics (e.g., Lee et al (2001), Hu et al (2008), Ozcan and Toklu (2010), and Yegul et al (2010)) and meta-heuristics (e.g., Kim et al (2000;, Baykasoglu and Dereli (2008), Simaria and Vilarinho (2009), Ozcan and Toklu (2009b), Ozcan (2010), Tapkan (2010, 2011), Rabbani et al (2012), Chutima and Chimklai (2012), and Purnomo et al (2013)) were proposed for balancing the two-sided assembly lines. Some exact solution approaches have also been presented by Wu et al (2008) and Hu et al (2010) to solve the two-sided assembly line balancing problem optimally.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that locating two straight lines in parallel helps minimize the total number of workstations. This was followed by other researches and new techniques have been developed for solving the problem (e.g., a shortest path approach by Benzer et al (2007), a tabu search algorithm by Ozcan et al (2009), an exact procedure by Scholl and Boysen (2009), a fuzzy goal programming model by Kara et al (2010), and ACO based approaches by Baykasoglu et al (2009) and ). The line parallelization idea has been applied to mixed-model lines and two-sided lines.…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde tek ve çok modelli montaj hattı dengeleme problemi için yasak arama algoritması ve yasak arama algoritmasına dayalı melez yaklaşımlar kullanılmıştır [27,28,29,30,31,32,33,34]. Bununla birlikte farklı montaj hattı yerleşimleri olan paralel [35,36,37], çift taraflı [38], paralel çift taraflı [39] ve U-tipi [40,41] montaj hattı dengeleme problemleri için de yasak arama yaklaşımı önerilmiştir. Ayrıca montaj hattı sıralama (assembly line sequencing) problemi için yasak arama yaklaşımı kullanılan çalışmalar da görülmektedir [42,43,44,45].…”
unclassified